One-step Hydrothermal Synthesis of Fe3O4/GO Composites Combined with Persulfate for the Removal of Reactive Black in Aqueous Solution - Sun, Zhaonan; Zhao, Wei; Wu, Jiayi; Shi, Ke; Zhang, Lin; Kou, Wei (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
An environmentally friendly magnetic Fe3O4/graphene oxide (Fe-GO) composite was synthesized via a hydrothermal method for persulfate (PDS) activation. The composite was systematically characterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and Brunauer-Emmett-Teller (BET) analysis. Furthermore, the degradation performance of reactive black 5 (RB5) in the composite/PDS system was investigated under varying conditions, including composite dosage, PDS concentration, initial RB5 concentration, solution pH, and oscillation frequency. The experiments showed that the RB5 removal efficiency could reach 99.2% with good reproducibility under the conditions of 0.8 g/L of composites, 3 mol/L of PDS, 200 r/min of stirring speed, pH = 6, and 25℃ for 180 min. Quenching experiments showed that four active reactive substances, sulfate radicals SO4-·), hydroxyl radicals (·OH), oxygen radicals (O2·−) and single linear oxygen (1O2), existed in the composite/PDS system, of which 1O2 played a crucial role in the degradation of RB5. Cycling tests showed that the Fe-GO composites were stable and had good application prospects. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).